(NsTARIJ ZAPOW)QÆT(B. (NbÆBLÆJNA ÆSTORÆQ (B/s)E - (Nb)QÆLOUSENKO(B, (No(B.,s)E; (NuLXQNOWSXKIJ(B, (Nw(B. )Qæ.,s)E; (NdENISOW(B, (Nr(B. (Nm(B.,s ((NkI)QÇW (B:s)E (NlIB)QÆDX(B,s)E, 1993)
(NkNIGA OSNOW W)QÆROW^ENNQ(B, Æ(NSTORÆQ sWQTOGO pISXMA(B, (NCERKOWNOSLUVÆNNQ(B, (NPÆDGOTOWLENA WIZNA^NIM UKRAÇNSXKIM U^ENIM ÃWROPEJSXKOGO RÆWNQ Æ PREKRASNIM DITQ^IM PISXMENNIKOM oLEKSANDROM lOTOCXKIM(B. ((NPSEWDONÆM (B- (NbÆLOUSENKO(B).s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NrEL)QÆGÆÃZNAWSTWOs)E -- )Qæ(NSTORÆQ RELÆGÆÇs)E -- (NhRISTIQNSTWOs; (NGR)QÆHs)E; (NOB)QÆTNICQs)E; (NpATR)QÆARHs)E; (NpROROKs